The Mackenzie River basin [electronic resource] - Camsell, Charles, 1876-1958.; Malcolm, Wyatt, 1872-1959.; Geological Survey of Canada. (Ottawa : J. de L. Taché, 1919)
Original issued in series: Memoir 108. Geological series / Geological Survey of Canada no. 92. At head of title: Canada. Department of Mines. Includes bibliographical references and an index. Electronic reproduction. Mode of access: Internet. 44